Neglected sexual dysfunction symptoms amongst chronic patients during routine consultations in rural clinics in the North West province - Deidre Pretorius; Ian D. Couper; Motlatso G. Mlambo (AOSIS, 2021)
Background: Sexual dysfunction contributes to personal feelings of loss and despair and being a cause of exacerbated interpersonal conflict. Erectile dysfunction is also an early biomarker of cardiovascular disease. As doctors hardly ever ask about this problem, it is unknown how many patients presenting for routine consultations in primary care suffer from symptoms of sexual dysfunction. Aim: To develop an understanding of sexual history taking events, this study aimed to assess the proportion of patients living with symptoms of sexual dysfunction that could have been elicited or addressed during routine chronic illness consultations. Setting: The research was carried out in 10 primary care facilities in Dr Kenneth Kaunda Health District, the North West province, South Africa. This rural area is known for farming and mining activities. Methods: This study contributed to a broader research project with a focus on sexual history taking during a routine consultation. A sample of 151 consultations involving patients with chronic illnesses were selected to observe sexual history taking events. In this study, the patients involved in these consultations completed demographic and sexual dysfunction questionnaires (FSFI and IIEF) to establish the proportions of patients with sexual dysfunction symptoms. Results: A total of 81 women (78%) and 46 men (98%) were sexually active. A total of 91% of the women reported sexual dysfunction symptoms, whilst 98% of men had erectile dysfunction symptoms. The youngest patients to experience sexual dysfunction were a 19-year-old woman and a 26-year-old man. Patients expressed trust in their doctors and 91% of patients did not consider discussion of sexual matters with their doctors as too sensitive. Conclusion: Clinical guidelines, especially for chronic illness care, must include screening for sexual dysfunction as an essential element in the consultation. Clinical care of patients living with chronic disease cannot ignore sexual well-being, given the frequency of problems. A referral to a sexual medicine specialist, psychologist or social worker can address consequences of sexual dysfunction and improve relationships.